2016
DOI: 10.1186/s12936-016-1121-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating malaria transmission intensity from Plasmodium falciparum serological data using antibody density models

Abstract: BackgroundSerological data are increasingly being used to monitor malaria transmission intensity and have been demonstrated to be particularly useful in areas of low transmission where traditional measures such as EIR and parasite prevalence are limited. The seroconversion rate (SCR) is usually estimated using catalytic models in which the measured antibody levels are used to categorize individuals as seropositive or seronegative. One limitation of this approach is the requirement to impose a fixed cut-off to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 50 publications
(51 reference statements)
0
49
0
Order By: Relevance
“…Fitting of antibody data to other models may also help improve on the predictive power of data from cross-sectional surveys. For example, recent sero-epidemiology studies have reported more precise parasite exposure rates based on new models that utilize continuous antibody data compared to seroconversion estimates by the catalytic model based on dichotomized antibody data [32,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Fitting of antibody data to other models may also help improve on the predictive power of data from cross-sectional surveys. For example, recent sero-epidemiology studies have reported more precise parasite exposure rates based on new models that utilize continuous antibody data compared to seroconversion estimates by the catalytic model based on dichotomized antibody data [32,38]. …”
Section: Discussionmentioning
confidence: 99%
“…; Pothin et al . ). As antibody levels decay rapidly over time in many wildlife host‐pathogen systems (especially in non‐mammalian hosts), there is opportunity to learn about temporal disease dynamics in a population by considering antibody levels in individual hosts.…”
Section: Introductionmentioning
confidence: 97%
“…; Pothin et al . ) that should be treated explicitly (Gay ; Vyse et al . ), and neglecting the potentially valuable information that can be gained from considering the quantitative antibody data (Bollaerts et al .…”
Section: Introductionmentioning
confidence: 99%
“…suggesting that measurement of EIR may be a relatively insensitive indicator of malaria transmission in some settings. Although malaria parasite prevalence and/or EIR have traditionally been used for reporting malaria transmission intensity [52], serological markers have increasingly been recognized as useful indicators for estimating malaria transmission intensity, which is key for assessing the impact of control interventions [53][54][55][56]. Because of the longevity of the specific antibody response, seroprevalence reflects cumulative exposure and thus is less affected by seasonality or unstable transmission [57].…”
Section: Discussionmentioning
confidence: 99%